The role of plant-breeding R&D in tractor adoptions among smallholders in Asia: Insights from Nepal Terai - Takeshima, Hiroyuki; Liu, Yanyan (International Food Policy Research Institute, 2018)
Combining agricultural census data from Nepal from 2001 and 2011 with various spatial agroclimatic data, we show that increase in yield potentials due to the introduction of high-yield technologies (particularly improved seed varieties) plays an important role in smallholders’ tractor adoption in Nepal Terai. We use a novel instrumental variable, agroclimatic similarity between farmers’ and plant breeding institutes’ locations, to instrument the adoption of improved seed varieties. To our knowledge, our study offers the first direct evidence that mechanization growth among smallholders is partly induced by the introduction of high-yield technologies.